Infâncias e educação infantil : redes de sentidosproduções compartilhadas no currículo e potencializadas na pesquisa com as crianças. - Nunes, Kezia Rodrigues (2012)
The purpose of this text consists in understanding the relationships between the concepts of child, childhood and upbringing. The text discusses, relates and also connects these concepts in order to erase their commom meaning. This way it updates what has been understood as the way they function together, to what they have become. The research uses two diferente sources: First, it looks into some graduate studies (specially Deleuze’s and Guattari’s) which approach these concepts relating them to the philosophy of difference. It gathers 13 articles published by Associação Nacional de Pós-Graduação e Pesquisa em Educação (Anped), 3 articles by Revista Brasileira de Educação (RBE) and also 12 graduate program education theses. The second one involves research performed in a CMEI in the city Cariacica/ES/Brazil during 2011. This research consisted in observing the conversation among seventy children between four and five years old, studying in the afternoon. It bases its methodology on the daily school research thoughts (ALVES 2008a, 2008b, AZEVEDO 2008, FERRAÇO 2003, 2007, 2008) and also on the cartography (KASTRUP 2007, DELEUZE; GUATTARI, 1995). The text uses different research tools, such as: a field journal, photographic and filmic records, chats with adults and children and also interview games created for the research. These tools allowed the research to stratify, to organize, to deterritorialize and to produce escape into these different concepts. Continuous intensity zones multiply the concepts into eight plateaus that extrapolate the final image in order to negociate with the children. It was noticed the children’s logic as far as the research mapped the children’s works and wishes, most of time, can’t be related to the adults’. This research allowed us to understand the children and their world better. It enabled us to connect to them, deeper than we could, considering our previous knowledge. The following concepts were considered in order to make the discussions relevant: The school as a meeting place; to play with one’s friends; to grow into diferente moments of childhood (such as: studying, reading, writing, painting, drawing, playing, creating, fabling, falling in love); to extend the chronological time into aiônico time; to cause experimentation that consider all children as unique and different beings; to expand the understanding of childhood considering its duration and potentiality; to induce dialogue about the childhood plays, to consider the children’s and school’s modulations according to the crying and dissatisfaction and other lines that get away. It is accepted that children summon us, incite us, challenge us, invite us to share other production networks, new demands, and other possibilities with them. Much more often than adults do. These concept’s de-re-territorialization consist on a political bid on a changing wish. One that considers the necessity of recreating ourselves in adults and children simultaneously. Turning the relations parallel in order to open the children’s demands, the regular ones and also the ones inside us, the adults.